Little brother - Doctorow, Cory (Tor Teen, 2008)
After being interrogated for days by the Department of Homeland Security in the aftermath of a major terrorist attack on San Francisco, California, seventeen-year-old Marcus, released into what is now a police state, decides to use his expertise in computer hacking to set things right.